2016
DOI: 10.14412/1995-4484-2016-171-174
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Levels of Angiotensin Ii, Aldosterone, and Fibroblast Growth Factor in Patients With Rheumatoid Arthritis in Relation to Clinical Features

Abstract: Клинические и экспериментальные исследования патофизиологии ренин-ангиотензин-альдостероновой системы (РААС) свидетельствуют о ее важной роли в развитии сосу-дистого воспаления, оксидативного стресса, эндотелиальной дисфункции и пролиферации фибробластов [1-3]. Установлено, что активация РААС ведет к развитию и хронизации вос-О р и г и н а л ь н ы е и с с л е д о в а н и я ГУ «Луганский государственный медицинский университет», Луганск 91045 Луганск, кв. 50-летия Обороны Луганска, 1г

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They significantly influence pathogenesis [16]. The important role of vascular lesions in the development of RA was confirmed by a number of studies [17,18].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They significantly influence pathogenesis [16]. The important role of vascular lesions in the development of RA was confirmed by a number of studies [17,18].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies confirmed that the blood level of ATII in patients with highly active RA was 1.5 times higher than in patients with low or moderate RA activity. Analysis of variance demonstrated that the degree of RA activity was associated solely with the blood level of ATII [17].…”
Section: Discussionmentioning
confidence: 97%